2004
DOI: 10.1158/1078-0432.ccr-04-0746
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Irinotecan, Infusional 5-Fluorouracil, and Leucovorin (FOLFIRI) with Erlotinib (OSI-774)

Abstract: Results: The study was halted after six patients at the lowest dose level due to unexpectedly severe toxicities, including disfiguring grade 2 rash (three patients), grade 3 diarrhea (three patients), and grade > 3 neutropenia (three patients). All patients required some dose interruption or reduction of either erlotinib or FOLFIRI, and only one patient completed two 6-week cycles of therapy. Five patients had stable disease after one cycle, and one patient had a partial response. No plasma pharmacokinetic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…These negative results may be due to a lack of efficacy of small molecules inhibitors of EGFR in combination with Figure 1 Kaplan -Meier plots for progression free survival. Gefitinib and FOLFOX in colorectal cancer S Cascinu et al chemotherapy as in colorectal cancer or to the lack of patient selection Herbst et al, 2004;Messersmith et al, 2004). A recent study by Zampino and co-workers also evaluated the combination FOLFOX-6 and gefitinib in a phase II trial including 56 patients.…”
Section: Discussionmentioning
confidence: 99%
“…These negative results may be due to a lack of efficacy of small molecules inhibitors of EGFR in combination with Figure 1 Kaplan -Meier plots for progression free survival. Gefitinib and FOLFOX in colorectal cancer S Cascinu et al chemotherapy as in colorectal cancer or to the lack of patient selection Herbst et al, 2004;Messersmith et al, 2004). A recent study by Zampino and co-workers also evaluated the combination FOLFOX-6 and gefitinib in a phase II trial including 56 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies, trastuzumab, bevacizumab, and IMC-A12 were each used at 1 Ag/mL. Erlotinib was used at 2 Amol/L, in keeping with previously reported clinical steady state plasma concentrations in the range of 2 to 4 Amol/L (44,45). These studies suggest that high HER2 -expressing breast cancer cell lines exhibit greater growth inhibition in response to trastuzumab, erlotinib, or bevacizumab, than the low HER2 -expressing cell lines over a range of concentrations.…”
Section: Her2 Expression In Human Breast Cancer Cell Linesmentioning
confidence: 99%
“…We propose that the interaction of irinotecan and gefitinib in our trial is likely to have been pharmacokinetic, resulting in greater than anticipated exposure to irinotecan and its active metabolite. Interestingly, Messersmith et al (2004) have recently reported excessive toxicity requiring early closure of the study in a phase I trial of a combination of erlotinib with reduced doses of irinotecan and infusional 5-FU. A pharmacokinetic interaction between irinotecan, 5-FU, and erlotinib could not explain the toxicity.…”
Section: Discussionmentioning
confidence: 99%